Influence of the surface treatment of tire rubber residues added in mortars - A. C. Marques; J. L. Akasaki; A. P. M. Trigo; M. L. Marques (Revista IBRACON de Estruturas e Materiais)
In this work it was evaluated the influence tire rubber addition in mortars in order to replace part of the sand (12% by volume). It was also intended to verify if the tire rubber treatment with NaOH saturated aqueous solution causes interference on the mechanical properties of the mixture. Compressive strength, splitting tensile strength, water absorption, modulus of elasticity, and flow test were made in specimens of 5cmx10cm and the tests were carried out to 7, 28, 56, 90, and 180 days. The results show reduction on mechanical properties values after addition of tire rubber and decrease of the workability. It was also observed that the tire rubber treatment does not cause any alteration on the results compared to the rubber without treatment.